Pattern of Provoking Factors and Psychiatric Co- morbidity in Migraine Headache: A Study from Tertiary Care Hospital - Khan, Tanveer Ahmed (Journal of Nepalgunj Medical College, 2018)
Introduction: Headaches are the most prevalent neurological disorders and among the most frequent symptoms seen in general practice among which migraine only accounts up to 30%. Certain factors are found to play role in the triggering of migraine headache. Avoidance of such factors is part of migraine management. Psychiatric co morbidities are common in migraine. Recognizing these co morbidities could therefore result in improved patient management. Methods: This study was done at Nepalgunj medical college hospital, Nepalgunj. Duration of study was six months i.e. from 1st July 2017 to 31st December 2017. All the new cases fulfilling diagnostic criteria of migraine headache visiting to psychiatric outpatient department were included in this study. The diagnosis of migraine was made based on criteria mentioned by the international classification of headache disorders (ICHD-II). Result: A total of 50 patients were enrolled in this study. The mean age of participants was 28.60 ± 10.388 years. There was significant predominance of female participants. Family history of migraine was found in 20 (40%) of participants. The mean age of onset was 22.76± 7.899 years. The commonest type of migraine was migraine without aura in 2/3rd number of cases. Psychiatric co-morbidity was found in 26 (52%) subjects among which the most common co-morbidity was anxiety disorder in 16 (32%) followed by depression in 8 (16%). Presence of provoking factors was found in 38 (76%) subjects. Light, smoke, smell, noise and lack of adequate sleep were the common provoking factors. Conclusion: Migraine predominantly affects females with common age of onset in second and third decade. Psychiatric co-morbidities are common in migraine patients. Anxiety disorder and depression are the commonest co-morbidities. The common provoking factors are light, smoke, smell, noise and lack of adequate sleep found in migraine. Avoidance of provoking factors and early detection and management of psychiatric co morbidities can result in better outcome.